1977
DOI: 10.1046/j.1537-2995.1977.17578014580.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Procedure for Deglycerolizing Red Blood Cells Frozen in a High Glycerol Concentration

Abstract: Although the high (40 to 50 per cent) glycerol method of freezing red blood cells has many advantages, no feasible procedure for deglycerolizing with only a clinical centrifuge has been available. Thus this method has been restricted to blood centers that distribute a sufficient number of frozen cells to warrant the installation of automated cell washing equipment. However, by sedimenting the glycerolized cells prior to freezing and discarding the excess glycerol solution, postthaw deglycerolizing can be simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…Fax: +49 511 762 19389. E-mail: wolkers@imp.uni-hannover.de high cooling rate is required (Smith 1950, Mollison and Sloviter 1958, Rowe et al 1968, Meryman and Hornblower 1977. One of the main disadvantages of these procedures is the deglycerolization step, which has to be implemented prior to transfusion into patients.…”
Section: Introductionmentioning
confidence: 99%
“…Fax: +49 511 762 19389. E-mail: wolkers@imp.uni-hannover.de high cooling rate is required (Smith 1950, Mollison and Sloviter 1958, Rowe et al 1968, Meryman and Hornblower 1977. One of the main disadvantages of these procedures is the deglycerolization step, which has to be implemented prior to transfusion into patients.…”
Section: Introductionmentioning
confidence: 99%
“…The step of removing CPAs may cause serious cell loss due to the cell volume excursion induced by osmotic disequilibria (Meryman, 2007). In the past decades, many efforts have been made to improve the process (Rowe et al, 1968;Meryman et al, 1972Meryman et al, , 1977Valeri et al, 1975Valeri et al, , 2001Castino et al,1996;Arnaud et al 2003).…”
Section: Results From Experimental Examinationmentioning
confidence: 99%
“…Currently, multi-step centrifuging methods are most commonly used, and some of them can achieve favorable results (Rowe et al, 1968;Meryman et al, 1972Meryman et al, , 1977Valeri et al, 1975Valeri et al, , 2001. However, the procedures are very difficult and time consuming for manual operation due to the large cell suspension volume or high CPA concentration.…”
Section: Results From Experimental Examinationmentioning
confidence: 99%
“…The original high glycerol / slow freeze process developed by Tullis and colleagues [4] has been greatly simplified whereby the red cells are now more easily glycerolized without use of a centrifugal bowl and can be frozen in the primary collection bag to optimize donor identification, particularly for autologous blood [5]. In addition, the deglycerolization process was greatly simplified by Meryman and Hornblower [3] who found that the red cells could be diluted with one or more salt solutions of different concentration and washed by either continuous-flow centrifugation or by automated batch centrifugation. This method with its many minor variations today is the one that is used most routinely in the United States as well as in the rest of the world for cryopreservation of blood for transfusion.…”
Section: High Glycerol / Slow Freeze Preservationmentioning
confidence: 99%